Justice and Non-Human Animals - Part I (Bangladesh Journal of Bioethics, 2016)
It is widely held that moral obligations to non-human beings do not involve considerations of justice. For such a view, nonhuman interests are always prone to be trumped by human interests. Rawlsian contractarianism comprises an example of such a view. Through analysis of such theories, this essay highlights the problem of reconciling the claim that humans have obligations to non-humans with the claim that our treatment of the latter is not a matter of justice. We argue that if it is granted that the basic interests of non-human beings sometimes count for more than the peripheral interests of humans, then our understandings of obligation and of justice must be aligned, so that what we say about obligation is not countered by assumptions about the invariable priority of humans in matters of justice. We further consider whether such a conclusion can be endorsed by those who adopt certain alternative theories to contractarianism. We conclude that adherents of a range of theories including sentientism and biocentrism must accept that human interests can sometimes be superseded by animal interests, and that this applies not least in matters of justice.